Erector Spinae Plane Catheter for Postoperative Analgesia After Thoracotomy in a Pediatric Patient: A Case Report. Issue 9 (1st May 2019) - Patel, Nihar V.; Glover, Chris; Adler, Adam C.
Abstract : Thoracotomy is associated with significant postoperative pain. While postoperative pain control after thoracotomy is most commonly managed with a thoracic epidural or paravertebral catheter, both are fraught with significant risks and are technically challenging to perform in pediatric patients. The erector spinae plane block is a relatively novel, easy-to-perform block used to provide thoracic wall analgesia. We present a case of a pediatric patient undergoing thoracotomy whose postoperative pain was managed with an erector spinae plane catheter.